Factors Influencing Smokeless Tobacco Use in Rural Communities of Bangladesh: Smokeless tobacco use in rural Bangladesh - Arifin, Umme Hamida; Hossain, Quazi Zahangir; Zaman, Qazi Azad uz (South Asian Journal of Agriculture, 2023)
Smokeless tobacco, SLT is a tobacco product used for chewing, sniffing, placing between teeth and gum. The situation and tradition of SLT use, influential personal and socio-cultural factors and awareness about harmful effect were observed from 552 SLT users using a semi-structured questionnaire for comparative analysis. Rural communities were selected in 2-districts where tobacco is cultivated traditionally (Kushtia) and tobacco is not cultivated (Khulna). Respondents’ mean age was 48.6±14.4 and about half without any formal education. Most of the respondents (92%) use SLT daily and among them three-fourths were the user of zarda followed by gul and sadapata. More number of respondents in Khulna use gul (27.9%) than Kushtia (20.7%), reversely sadapata is used more in Kushtia (22.1%) compared to Khulna (11.9%). Almost half of the respondent’s (45.7%) parents and wives (41.7% and 32.6% respectively) were more likely to use SLT in Kushtia (37.0%) than in Khulna (30.0%). Only 13.0% of the respondents were influenced to intake SLT by their family members. The reasons behind consuming SLT as mentioned by the respondents in Khulna are to reduce depression (32.7%), remove mouth odor (27.7%) and control vomiting (19.8%). Irrespective of the locations, almost half of the respondents (47.3%) were influenced by social factors such as peer group (79.3%) and gossiping partners (64.4%). It was also noted that, 95.8% of the respondents offer SLT to the guests during the wedding ceremony. A good portion of the respondents (84.6%) believe that SLT has harmful effects as they got such information from product cover (31.7%), medical professionals (23.6%) and television (14.1%). About 40% of the respondents believe that cancer may be caused by regular consumption of SLT, though yet they use SLT for the remedy from toothache and gum pain (31.9%), on peer pressure (28.6%) and for amusement only (10.1%). It could be concluded that, the use of SLT in the study areas is at an alarming level which should be noticed by the concerned authority to control the promotional activities and to imposing restrictions on the availability of SLT as traditional items. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 11-21